Little Circle Arabic Learning (LCAL) To Improve Arabic Language Skills And Confidence/ Little Circle Arabic Learning (LCAL) Untuk Meningkatkan Kemampuan Berbahasa Arab Dan Kepercayaan Diri - Mauludiyah, Lailatul; Syarofah, Alfiatus; Fauzi, Moh. Fery (Ijaz Arabi Journal of Arabic Learning, 2021)
Learning Arabic at the university level for non-language majors was still a problem, and it was still being developed. This research aimed to see how well the Little Circle Arabic Learning (LCAL) learning model worked in practice. Students majoring in Islamic Religious Education who are learning the native language at the University of Muhammadiyah Malang's Arabic Language Development Program (PPBA) were the subject of this study, which used a quantitative approach. The method of data collection were questionnaires and tests. While the data analysis used is descriptive quantitative to process the results of the questionnaire. The sample t-test is related to processing the test results. Based on the t-test results, this research indicates that the Little Circle Arabic Learning (LCAL) model effectively taught Arabic at the university level. There was also an increase in competence in students in terms of kalam, vocabulary, and translation. This LCAL learning model can also improve the ability to interact with teams in groups and the student's self-confidence. These components support students being able to speak Arabic.